1998
DOI: 10.1124/mol.53.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Chloroethylclonidine Binds Irreversibly to Exposed Cysteines in the Fifth Membrane-Spanning Domain of the Human α2A-Adrenergic Receptor

Abstract: The alpha2-adrenergic receptors (alpha2-ARs) mediate signals to intracellular second messengers via guanine nucleotide binding proteins. Three human genes encoding alpha2-AR subtypes (alpha2A, alpha2B, alpha2C) have been cloned. Several chemical compounds display subtype differences in their binding and/or functional activity. Site-directed mutagenesis and molecular modeling are new tools with which to investigate the subtype selectivity of ligands. In this study, we introduce a new approach to mapping of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…In our previous study, TM5 of H␣2A was shown to be consistent with an ␣-helix with residues Val-197, Cys-201, and Ser-204, pointing into the binding-site crevice, residues Ile-198, Ser-199, Ile-202, and Gly-203, facing the lipid bilayer, and Ser-200, pointing partly toward TM4 (9). Surprisingly, the pattern of accessibility to MTSEA in TM5 of the dopamine D2 receptor was not consistent with a fixed ␣-helical structure for TM5 (8).…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In our previous study, TM5 of H␣2A was shown to be consistent with an ␣-helix with residues Val-197, Cys-201, and Ser-204, pointing into the binding-site crevice, residues Ile-198, Ser-199, Ile-202, and Gly-203, facing the lipid bilayer, and Ser-200, pointing partly toward TM4 (9). Surprisingly, the pattern of accessibility to MTSEA in TM5 of the dopamine D2 receptor was not consistent with a fixed ␣-helical structure for TM5 (8).…”
mentioning
confidence: 86%
“…Mutagenesis and Expression Vectors-Site-directed mutagenesis was performed utilizing the Altered Sites II in vitro mutagenesis system (Promega, Madison, WI) as described previously (9). The wild type H␣2A and the mutated receptor cDNAs were subcloned into the KpnI/ BamHI sites of the expression vector pREP4 (In Vitrogen, NV Leek, The Netherlands).…”
Section: Materials-[mentioning
confidence: 99%
See 3 more Smart Citations